From surplus-to-waste: A study of systemic overproduction, surplus and food waste in horticultural supply chains. (1st January 2021) - Messner, Rudolf; Johnson, Hope; Richards, Carol
Abstract: Until recently, food waste prevention intervention has largely offered 'end of pipe solutions' that focus on causes of food waste at specific points in supply chains and on dealing with the physical waste material itself. Recent research has taken a different approach by emphasizing the systemic nature of the food waste problem and the need for its in-depth exploration. This paper offers a systems-based understanding of food waste, which allows for an account of the interconnected processes that underpin waste creation along the whole supply chain. Through a qualitative inquiry on practices and processes of surplus and waste creation in the Australian horticulture industry, the research findings precisely delineate 'surplus-to-waste lock-ins'. That is, the institutional, cultural, and material factors that enable the creation of food waste through the related categories of over-production and surplus formation. The article's identification and analysis of surplus-to-waste lock-ins is grounded in a socio-technical transitions perspective and extends transition studies to agrifood systems and horticultural food waste. This research positions systemic food waste theoretically as a symptom of 'system-lock-in', which may thwart efforts to prevent food waste, and thus bridges micro and macro levels of analysis. These findings translate into three key recommendations for industry, policy and research: that approaches addressing systemic processes of waste creation are essential to unlocking food waste prevention, that food waste prevention should target the identified system processes contributing to food chain lock-ins, and that transparent monitoring and disclosure of food surplus is a prerequisite for systemic food waste prevention across the whole supply chain. Graphical abstract: Image 1 Highlights: Australian horticulture supply chains encourage production of food surplus while lacking mechanisms for food waste prevention. Food waste creation is reinforced by powerful lock-in mechanisms that both rely on surplus and resist reducing surplus. Systemic food waste prevention must target the processes of food waste creation along the entire supply chain. Transparent monitoring and disclosure of surplus in food chains is an essential prerequisite of food waste prevention.